PECULIARITIES OF FORMING THE COMPETENCES OF STUDENTS IN SEWING AND SERVICE INSTITUTIONS (Innovative professional education, 2025)
The article considers modern approaches to the formation of competencies in students of a vocational education institution. New regulatory documents regulating the activities of vocational education institutions and their impact on the educational process are analyzed. Special attention is paid to the implementation of dual education, digitalization of training and integration of key and professional competencies
Keywords: vocational education, key and professional competencies, dual learning, digitalization of the world, development of technologies, competencies of students, educational institution